Remote Monitoring for the Operation Status of CNC Machine Tools Based on HTML5 - Wang, Yu-Shun; He, Ling-Song; Gao, Zhi-Qiang; Wang, Jun-Feng; Cao, Yang-Fan (Advances in Technology Innovation, 2019)
In order to improve the accuracy of remote monitoring of computer numerical control (CNC) machine tools and reduce the difficulty of monitoring; a remote monitoring method for CNC machine tools based on HTML5 is proposed in this paper. The core idea of this method is to record external sensor information and internal working condition information in the same time, and then visualize the information in multiple directions. Monitoring accuracy is improved through the combined use of internal and external information. In response to the difficult problem of traditional method monitoring; the internal working condition information, external sensor information, 3D model and multimedia information of CNC machine tools are jointly visualized. The 3D model synchronous motion is driven by real-time working condition data. Remote low-latency multimedia information transmission is implemented by using cloud live broadcast technology.